2013
DOI: 10.2147/cia.s44834
|View full text |Cite
|
Sign up to set email alerts
|

Results of cataract surgery in the very elderly population

Abstract: AimThe aim of our study was to retrospectively evaluate the effectiveness and safety of cataract surgery and intraocular lens implantation (IOL) for patients aged 90 years or older, whom we define as “very elderly.”MethodsThe study involved a total number of 122 patients (122 eyes) with senile cataracts. The mean age of patients was 91.2 ± 2.3 years (range 90–100 years old). Phacoemulsification (phaco) was done on 113 of 122 eyes, and 9 of 122 eyes had extracapsular cataract extraction (ECCE). Postoperative vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Previous smaller studies on elderly people have reported similar visual changes. Michalska et al, (22) in their study of 122 operations on patients over 90 years of age, reported that postoperative VA improved in 84% eyes, remained the same in 16% eyes and deteriorated in 1.6% eyes, this deterioration being attributed in 62% of the cases to the underlying advanced AMD. The figure of 84% for VA improvement in this small study was virtually identical to the 85% reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous smaller studies on elderly people have reported similar visual changes. Michalska et al, (22) in their study of 122 operations on patients over 90 years of age, reported that postoperative VA improved in 84% eyes, remained the same in 16% eyes and deteriorated in 1.6% eyes, this deterioration being attributed in 62% of the cases to the underlying advanced AMD. The figure of 84% for VA improvement in this small study was virtually identical to the 85% reported here.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report found no difference in postoperative VA between 31 eyes of patients aged ≥90 years and 70 eyes of patients aged < 90 years [ 13 ]. Other recent studies also have shown favorable VA outcomes after cataract surgery in patients aged ≥90 years, though without comparison to younger patients [ 14 , 15 ]. Another limitation is that these previous studies have used postoperative VA as an outcome measure, but not improvement in postoperative VA.…”
Section: Discussionmentioning
confidence: 99%
“…5 Despite rapid increase in the availability of quality cataract services, however, surgical acceptance is still low in the community. [1][2][3][4][5][6] Studies have shown that availability of eye care services may not necessarily translate into their effective and adequate utilisation. 7 For example, in the state of Goa, ours is a government funded tertiary care centre providing cataract surgery services.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when systemic conditions are stable, both phacoemulsification and Extra-capsular cataract extraction (ECCE) with intraocular lens (IOL) implantation for very elderly patients are effective and safe. 4 However, with an earlier treatment, better visual outcomes would become more achievable even in those with co-existing ocular and systemic illnesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation